The role of Cost awareness of activation of strategic cost management techniques of industrial units: A prospective study at the General Company for the manufacture of medicines and medical supplies in the province of Mosul (Journal of Accounting and Financial Studies ( JAFS ), 2012)
The last ten years observed a shift enormous scientific in the method and way that it deals professional with the cost accounting and reflected the result those shift enormous scientific of increase the competitive environmental that accompanied the emergence of a modern manufacturing environmental on surface the long roductive life and emergence advanced information technology that give a central focus of his important on client with growing global markets growth on a large scale.        The research aim to define the concept of cost awareness, the concept and methods of  strategic cost management and the role of cost awareness for managers of industrial units in strategic of cost management, the research premise that growing of cost awareness upon managers of industrial units will lead to provide the necessary environmental for development of efficient management of costs and then increase the effectiveness of the costs information systems.   This research find out the set of conclusions one of most important is that publishing the cost awareness and growing it at management of companies help greatly on applying the methods of strategic cost management. The researchers  recommended the needed of growing and publishing cost awareness concept at companies management and trend towards apply the methods of strategic  cost management.